Does Fiscal Decentralization Improve Health Outcomes? Evidence from a Cross-Country Analysis - Robalino, David A.; Picazo, Oscar F.; Voetberg, Albertus (World Bank, Washington, DC, 2014)
Decentralization of fiscal responsibilities has emerged as a primary objective on the agendas of national governments, and international organizations alike. Yet there is little empirical evidence on the potential benefits of this intervention. The authors fill in some quantitative evidence. Using panel data on infant mortality rates, GDP per capita, and the share of public expenditures managed by local governments, they find greater fiscal decentralization is consistently associated with lower mortality rates. The results suggest that the benefits of fiscal decentralization are particularly important for poor countries. They suggest also that the positive effects of fiscal decentralization on infant mortality, are greater in institutional environments that promote political rights. Fiscal decentralization also appears to be a mechanism for improving health outcomes in environments with a high level of ethno-linguistic fractionalization, however, the benefits from fiscal decentralization tend to be smaller.